2020
DOI: 10.1002/rth2.12355
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activation in the musculoskeletal acute phase response: Injury, repair, and disease

Abstract: The musculoskeletal system is critical for movement and the protection of organs. In addition to abrupt injuries, daily physical demands inflict minor injuries, necessitating a coordinated process of repair referred to as the acute-phase response (APR). Dysfunctional APRs caused by severe injuries or underlying chronic diseases are implicated in pathologic musculoskeletal repair, resulting in decreased mobility and chronic pain. The molecular mechanisms behind these phenomena are not well understood, hindering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 98 publications
(190 reference statements)
0
15
0
1
Order By: Relevance
“…Activation of blood coagulation and innate immune response was indicated in Sol muscles of mice exposed to μ- g , regardless of FOS ingestion (Table 8 and Supplementary Tables 3a and 4a ), which had not been reported in previous studies 16 , 37 . In addition to these biological processes, fibrinolysis is also reportedly activated in response to skeletal muscle injury and has important role in the initial phase of repair 48 52 . However, negative regulation of fibrinolysis was indicated, especially in Sol muscles of mice exposed to μ- g without FOS ingestion, by the significant increase in Apoh, Plg, Serpinf2, and Hrg (Table 8 and Supplementary Table 3a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of blood coagulation and innate immune response was indicated in Sol muscles of mice exposed to μ- g , regardless of FOS ingestion (Table 8 and Supplementary Tables 3a and 4a ), which had not been reported in previous studies 16 , 37 . In addition to these biological processes, fibrinolysis is also reportedly activated in response to skeletal muscle injury and has important role in the initial phase of repair 48 52 . However, negative regulation of fibrinolysis was indicated, especially in Sol muscles of mice exposed to μ- g without FOS ingestion, by the significant increase in Apoh, Plg, Serpinf2, and Hrg (Table 8 and Supplementary Table 3a ).…”
Section: Resultsmentioning
confidence: 99%
“…This result could be attributed to differences in the time of activation of these processes. One of the important roles of fibrinolysis is to remove fibrin deposited after blood coagulation for subsequent tissue repair, thus blood coagulation precedes the activation of fibrinolysis 48 . These results suggested that Sol muscles of mice exposed to μ- g were injured by gravitational reloading.…”
Section: Resultsmentioning
confidence: 99%
“…Due to advances in critical care medicine, patients now survive severe injuries, such as burn, blast, or polytraumatic injuries, that were once considered fatal. While being fortunate to survive, many patient experience complications during convalescence, including poor tissue repair, and hemostasis ( Gibson et al, 2020 ; Alessandrino and Balconi, 2013 ; Smith et al, 2000 ; Ferguson et al, 2008 ). While severely injured 2 patients are beleaguered by a variety of systemic derangements, one of the more paradoxical complications involves the dysregulation of biomineralization ( Muschitz et al, 2017 ; Klein, 2006 ; Vanden Bossche and Vanderstraeten, 2005 ; Dey et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following an injury, the acute phase response (APR) is activated in proportion to the injury severity ( Gibson et al, 2020 ; Benvenuti et al, 2017 ; Baker et al, 2018 ). To ensure survival, the APR first activates coagulation and an acute inflammatory response to stop bleeding and prevent infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation